Mechanistic study on the susceptibility of Staphylococcus aureus to common antimicrobial preservatives mediated by wall teichoic acids - Xia Wu; Jiayi Wang; Ji Li; Zheng Su; Jian Zha (Applied and Environmental Microbiology, 2025)
ABSTRACT Staphylococcus aureus is a common food-borne pathogen that easily develops resistance to antibiotics and antimicrobial peptides partly because of wall teichoic acids (WTAs), the peptidoglycan-anchored polymers important for cell physiology. In the food industry, there is an increasing prevalence of S. aureus despite the widespread use of antimicrobial preservatives, and it remains elusive how WTAs affect the susceptibility of S. aureus to these preservatives. In this study, we first identified that the presence of WTAs altered S. aureus sensitivity to tea polyphenol, sodium dehydroacetate, and ε-polylysine after screening 14 frequently used antimicrobial food preservatives. Then, via a series of genetic and biochemical analyses combined with molecular dynamics simulation, we revealed three WTA-related mechanisms adopted by S. aureus for self-protection against sodium dehydroacetate and ε-polylysine: (i) charge repulsion mediated by D-alanylation to reduce preservative packing around the cell; (ii) hydrogen bonding and hydrophobic interactions involving WTA backbone and glycosylation to maintain the preservatives in the WTA layer and to reduce their passage across the cell membrane; (iii) steric hindrance to reduce cell wall permeability and minimize the contact of these antimicrobials with the cell membrane. In comparison, the latter two mechanisms were involved in cell interaction with tea polyphenol. This work highlights the complex roles played by WTAs in cell response to antimicrobial preservatives and provides guidance to further study on S. aureus tolerance to food preservatives and better control over food safety.IMPORTANCEStaphylococcus aureus is a disease-causing bacterium frequently detected in raw and packaged food that can be strongly insensitive to many bacteria-inhibiting or bacteria-killing agents. With the widespread use of antimicrobial food preservatives during food processing and packaging, there is a potential risk that these preservatives may force S. aureus to become less sensitive. Given that S. aureus tolerates many antimicrobial agents using mechanisms related to wall teichoic acids (WTAs), the negatively charged polymers that are anchored in the cell wall of this bacterium, it is necessary to evaluate whether S. aureus presents WTA-dependent sensitivity to antimicrobial food preservatives and how WTAs affect S. aureus interaction with these preservatives. Our study answered these questions for tea polyphenol, sodium dehydroacetate, and ε-polylysine and revealed three WTA-related mechanisms including charge repulsion, surface trapping, and decline in cell wall permeability. This work emphasizes the need for further control over food safety.